The importance of complexities of scale and context in fisheries research and management. (27th September 2022) - Ommer, Rosemary E; Perry, R Ian
Abstract: Problems with spatial (geographical) and temporal scales in fisheries research and management have become better known over the past few years. However, technological and some institutional scales, along with essential contextual dimensions (policy, intellectual, and academic) are also important. We discuss fisheries management in general with respect to these matters and their interactions. We also provide recommendations for addressing these issues, both in general and with particular reference to local fisheries. These are: (1) recognize the importance of fishers' knowledge across all scales; (2) recognize fishers' motivations, especially at the local/community scale; (3) thus expand the nature of the information used for management; (4) match the spatial management scales to those of the fish and the fishers; (5) recognize the limitations of large institutions to manage fisheries at local scales; (6) recognize the limits of time-series data; and (7) develop better indicators for fishing effort.